Pengaruh Brand Awareness, Brand Image, dan Social Media Marketing Terhadap Purchase Intention (Studi Pada Toko Thrift 7Club Treasure di Kota Denpasar) - Tirtayoga, I Ketut Ogi; Wardana, I Made (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2024)
This research aims to determine the influence of brand awareness, brand image and social media marketing variables on purchase intention at the 7Club Treasure Thrift Store in Denpasar City. The theoretical basis for this research is Consumer Behavior Theory and the sampling method in this research was non-probability sampling using purposive sampling technique with 140 respondents. The data in this research was obtained through distributing research questionnaires directly to respondents. The analysis technique used is descriptive analysis and inferential analysis including multiple linear regression analysis, classical assumption test, simultaneous test (F test) and partial test (t test). The research results show that brand awareness has a positive and significant effect on purchase intention; brand image has a positive and significant effect on purchase intention; social media marketing has a positive and significant effect on purchase intention; and the three variables simultaneously influence purchase intention. The implications of this research are that brand awareness, brand image and social media marketing can be considered as an effort to increase purchase intention at the 7Club Treasure Thrift Store in Denpasar City. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh variabel brand awareness, brand image, dan social media marketing terhadap purchase intention pada Toko Thrift 7Club Treasure di Kota Denpasar. Landasan teori dalam penelitian ini adalah Teori Perilaku Konsumen dan metode penentuan sampel dalam penelitian ini adalah non probability sampling dengan menggunakan teknik purposive sampling dengan responden sebanyak 140 orang. Data dalam penelitian ini diperoleh melalui penyebaran kuesioner penelitian secara langsung kepada responden. Teknik analisis yang digunakan adalah analisis deskriptif dan analisis inferensial meliputi analisis regresi linier berganda, uji asumsi klasik, uji simultan (uji F) dan uji parsial (uji t). Hasil penelitian menunjukkan bahwa brand awareness berpengaruh positif dan signifikan terhadap purchase intention; brand image berpengaruh positif dan signifikan terhadap purchase intention; social media marketing berpengaruh positif dan signifikan terhadap purchase intention; dan ketiga variabel berpengaruh secara simultan terhadap purchase intention. Implikasi dari penelitian ini yaitu brand awareness, brand image, dan social media marketing dapat dipertimbangkan sebagai upaya meningkatkan purchase intention pada Toko Thrift 7Club Treasure di Kota Denpasar. Kata Kunci: Brand Awareness, Brand Image, Social Media Marketing, Purchase Intention